Prevalence of ectoparasites of carp fingerlings at Santaher, Bogra (University Journal of Zoology, Rajshahi University, 2009)
The research work was conducted to find out the seasonal prevalence of ectoparasites of carp fingerlings. Seven species of parasites viz. Trichodina domerguei, Trichodina reticulata, Chilodonella cyprini, Myxobolus koi, Dactylogyroides tripathi, Dactylogyrus extensus and Dactylogyrus catlarius were recovered from 640 fingerlings of Silver carp (Hypophthalmicthys molitrix), Bighead carp (Ctenopharyngodon idella), Common carp (Cyprinus carpio), Thai punti (Puntius gonionotus), Catla (Catla catla), Rui (Labeo rohita) and Mrigal (Cirrhina mrigala) from different nursery ponds of Bogra district during June 2005 to May 2006. The highest prevalence (95%) was in Trichodina domerguei and lowest (10%) in Dactylogyrus catlarius during winter season. Average prevalence of protozoan and monogenean parasite was 37.16 in rainy season, 40.08 in winter season and 30.25 in summer season. Winter is the most disease occurring season of the year. Key words: Ectoparasite, infestation, prevalence, fingerling, nursery pond Â  doi:10.3329/ujzru.v27i0.1947Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 17-19